1977
DOI: 10.1080/07435807709052938
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of FSH on LH Induced Testosterone Secretion in the Immature Hypophysectomized Male Rat

Abstract: The effect of gonadotropin pretreatment of hypophysectomized male rats on LH stimulated serum testosterone concentrations was studied. A 5 day pretreatment period began 2 days after hypophysectomy at 21 or 24 days of age. On the day following the pretreatment period the animals received an intraperitoneal injection of saline or LH 60 min before blood collection. Animals pretreated with NIH-FSH-B1, or with doses of LH approximating the amount present in the NIH-FSH, had increased testosterone concentrations aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
2
9
1
Order By: Relevance
“…Because this same human FSH preparation was highly active in FSH receptortransfected cells investigated during another study [15], there could be no doubt regarding its biological activity. Thus, our observations noting a lack of direct effect on the mouse testis (Leydig cells) is contradictory to those of several earlier studies in which investigators noted that FSH stimulated testosterone production both in vivo [2,19] and in vitro [3,20]. However, such effects may be due to the LH contamination in the FSH preparations, because these studies predate the availability of recombinant FSH [5].…”
Section: Discussioncontrasting
confidence: 99%
“…Because this same human FSH preparation was highly active in FSH receptortransfected cells investigated during another study [15], there could be no doubt regarding its biological activity. Thus, our observations noting a lack of direct effect on the mouse testis (Leydig cells) is contradictory to those of several earlier studies in which investigators noted that FSH stimulated testosterone production both in vivo [2,19] and in vitro [3,20]. However, such effects may be due to the LH contamination in the FSH preparations, because these studies predate the availability of recombinant FSH [5].…”
Section: Discussioncontrasting
confidence: 99%
“…Although receptors for FSH on the Sertoli cells are well established (Means and Vaitukaitis, 1972;Means et al, 1976;Orth and Christensen, 1977), the evidence for FSH receptors on Leydig cells is equivocal. It is generally agreed that FSH exerts its effect on Leydig cells by modulating LH receptors (Odell et al, 1973;Chen et al, 1976Chen et al, , 1977Odell and Swerdloff, 1976;Selin and Moger, 1977). Our studies regarding positive staining for FSH on Leydig cells are in agreement with the observation of Yoon et al (1987).…”
Section: Discussionsupporting
confidence: 90%
“…The rats were also hypophysectomized at an earlier age (21-25 days) than the present study; this is a critical period for Leydig cell development and these small differences in age may therefore be important. Selin & Moger (1977) found that 1-5 µg LH/day, a dose comparable to that which we used, resulted in a significant increase in the subsequent testicular response of hypophysectomized rats to LH in vivo. However, the effect was not as great as that with FSH (42-5 µg/day) which contained this quantity of LH as contamination.…”
Section: Discussionsupporting
confidence: 52%
“…This consideration has largely been prompted by the finding that FSH treatment of hypophysectomized rats results in an increase in the maximum quantity of LH-stimulated androgen secretion by Leydig cells, both in vivo (Odell & Swerdloff, 1975;Selin & Moger, 1977) and in vitro (Chen, Payne & Kelch, 1976;van Beurden, Roodnat, de Jong, Mulder & van der Molen, 1976;Chen, Shaw & Payne, 1977). Furthermore, FSH also appears to stimulate the number of LH receptors in testis tissue (Chen et al, 1977).…”
Section: Introductionmentioning
confidence: 99%